An analysis of the transformations of leadership and direction-setting in place marketing: a UK contextual view and case study. (2018) - Scott, Peter; Higson, Phil; Fletcher, Tom; Stokes, Peter
The marketing of places has experienced challenges in recent years. Prolonged and severe financial constraints have led to a considerable reduction in the public sector funding of initiatives. This is presenting new leadership imperatives. This paper elaborates place marketing and its changing identity and considers the nature and increasing need for effective leadership in the marketing of places. The study adopts an inductive approach and employs semi-structured interviews with senior executives from a range of destination marketing organisations. The research is contextualised within the UK and it uses places in North-West England to provide its focal setting developing two case studies with which to complement the wider data. The study identifies that the complexity of place marketing intertwined with financial pressures, creates a particular dynamic and a need for leadership to clarify, decode and respond to the resulting situations. The evidence presented points to a compelling need for leaders in the sector to accept and embrace the new realities and to provide a clear vision for the future.